A haplotype of cyclooxygenase-2 gene is associated with idiopathic pulmonary fibrosis - Xaubet, A.; Fu, W.J.; Li, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Cyclooxygenase-2, a key regulatory enzyme in the synthesis of the antifibrotic agent prostaglandin E2, is downregulated in lung tissue from patients with idiopathic pulmonary fibrosis. Objective: To investigate the association between COX2.3050 (G → C), COX2.8473 (C →T) and COX2.926 (G → C) single nucleotide polymorphisms (SNP) and the susceptibility to idiopathic pulmonary fibrosis and the progression of the disease. Design: Genetic polymorphisms were analyzed in 121 out of 225 available control subjects and in all of 174 patients with idiopathic pulmonary fibrosis by real time polymerase chain reaction. Logistic regression, analysis of covariance and chi-squares test were used for statistical analysis. Results: While analysis of disease development did not find any significant association with single SNP genotype, a haplotype analysis revealed a strong association between the disease development and one haplotype [GC] at loci COX2.3050 and COX2.8473, and suggested a recessive genetic effect of this haplotype. Further analysis concluded that subjects having two copies of [GC] haplotype, or equivalently (GG/CC) genotype at the two SNPs, had an increased risk after adjusting for age and sex. Due to the interaction, this elevated risk increased slowly with age, and the estimated odds ratio (OR) decreased with age from OR = 1.4 at age 30 to OR = 1 at age 74 and OR = 0.96 at age 80.The OR was significantly greater than 1 up to age 66, and not significant for age older than 66.Therefore, the recessive effect of [GC] haplotype increased the risk of IPF of subjects younger than 66 years, but its effect diminished for seniors older than 66. One hundred and forty-nine patients with idiopathic pulmonary fibrosis were followed up for 33.7 ± 2.1 months. Further analysis of disease progressions, defined by the changes in pulmonary function tests, did not reveal any association with either SNP genotypes or haplotypes. Conclusions: The carriage of double homozygote (GG/CC) at the SNP loci of COX2.3050 and COX2.8473 polymorphisms may increase the susceptibility to idiopathic pulmonary fibrosis, by approximately 1.4 folds at age 30 and by a smaller fold greater than 1 up to age 66 years, but not the progression of the disease. These findings may help to improve our understanding of idiopathic pulmonary fibrosis pathogenesis and may lead to the development of new therapeutic strategies.